Morphology of Sella Turcica and Bridging Prevalence Correlated with Sex and Craniofacial Skeletal Pattern in Eastern Asia Population: CBCT Study. (23rd March 2021) - Chou, Szu-Ting; Chen, Chun-Ming; Chen, Ping-Ho; Chen, Yuk-Kwan; Chen, Shis-Chieh; Tseng, Yu-Chuan
Abstract : Purpose . Sella turcica bridging (STB) refers to a rare anatomical variation formed by the ossification of the ligament between the anterior and posterior clinoid processes. The presence of the STB was significantly correlated with craniofacial skeleton classification and a higher prevalence rate in skeletal Class III. The current study is aimed at investigating the dimensions of sella turcica and the prevalence of STB in different sexes and on the three craniofacial skeletal patterns using cone beam computed tomography (CBCT). Materials and Methods . A total of 159 adults (66 males and 93 females), including 3 different craniofacial skeletal patterns (skeletal Classes I, II, and III), were included in the study. The sella turcica dimensions and the prevalence of STB were calculated. An independent t -test and generalized linear model were used to compare the differences in the sella turcica dimensions and the skeletal relations. The Spearman rank correlation coefficient was used to analyze the correlations between sella turcica dimensions and skeletal relation. Results . The sella length (SL) was 11.05 ± 1.80   mm for males and 10.77 ± 1.56   mm for females. The anterior clinoid distance (ACD) which was measured for the anterior width of sella turcica showed 25.83 ± 2.04   mm and 24.04 ± 2.28   mm for males and females, respectively (p < 0.0001 ). The overall percentage of complete bridging and partial bridging was 6.6% and 56.9%, respectively. Complete bridges were more common in males (males: 9.1%, females: 4.8%), and partial bridges were more frequent in females (males: 49.2%, females: 62.4%). Both sexes differed with respect to sella turcica dimensions. Moreover, males had a significantly larger ACD, posterior clinoid distance (PCD), and diameter of sella turcica (DST), on both sides, relative to females. Conclusion . The prevalence rate of complete STB in the Taiwanese population was 6.6%. Significant differences between sexes were found in sella turcica dimensions. The prevalence rates of STB as well as the sella turcica dimensions did not significantly differ between different craniofacial skeletal patterns (skeletal Classes I, II, and III).